Illegible Will : Coercive Spectacles of Labor in South Africa and the Diaspora - Young, Hershini Bhana (Book collections on Project MUSE., 2017)
Hershini Bhana Young engages with the archive of South African and black diasporic performance to examine the absence of black women's will from that archive, showing that alternative critical imaginings juxtaposed against traditional historical research can help to locate where agency and will may reside.